If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4m-2(2m+7)=-8m-13
We move all terms to the left:
-4m-2(2m+7)-(-8m-13)=0
We multiply parentheses
-4m-4m-(-8m-13)-14=0
We get rid of parentheses
-4m-4m+8m+13-14=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation
| 2t+2t-3t+2t-t=18 | | 15+1/2x=25+1/4x | | 8=8v-4(v+8)-32 | | 2.8=-10n+7.2 | | y-113=76 | | 4q+4q-2q+q=7 | | 12n-11=37 | | p/2+2=2 | | 3(x-4)+6x=15 | | 12p-6p-p=20 | | 5x/34=2x/5 | | 5c+10=100 | | -4.58=q-7.18 | | 3/4(12k-16)+2=26 | | 8L=(20-z)=87 | | (3x+4)/6+(x+18)/6=(x+8)/4 | | 2.7=3c-3(6-2c) | | b-295=337 | | 5x-7(-x)=34 | | 83=m-5 | | 3(2x-1)-4(x-2)=0 | | 83=x-5 | | 8-0.25•-76=a | | 2k=5.82 | | -2=-2=-(n-8) | | -72/p=9 | | 900=3x+4x+5x | | 3d+4=2=+3d-1/2 | | p/4=-2 | | t+38=72 | | 2x(x+5)-7=17 | | d-7.34=-4.41 |